The Role of Good Governance in Strengthening Public Administration Nepalese Perspectives (PAAN Journal, 2025)
Good governance is a cornerstone of effective public administration, promoting transparency, accountability, and inclusivity in government operations. This paper delves into the theoretical foundations of good governance and its role in public administration, drawing on global best practices and their applicability to Nepal. Key governance models, such as Network Governance, Weberian Bureaucracy, and New Public Management are examined alongside Nepal's governance challenges, including corruption, bureaucratic inefficiency, and decentralization issues. Recommendations are provided for institutional reforms, capacity building, and e-governance technologies to align Nepal's governance structures with international standards. The article highlights how fostering public trust, efficiency, and citizen participation can strengthen public administration, ultimately improving governance outcomes in Nepal.